Pengaruh Penggunaan Bahasa Gaul Terhadap Kemampuan Bahasa Indonesia Formal Di Kalangan Remaja - Fitri Syarifatul Holis (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Slang is a rapidly growing linguistic phenomenon among Indonesian teenagers, especially in daily interactions and social media usage. This widespread use of slang is predicted to impact teenagers' formal language skills, particularly in the context of proper and correct Indonesian. This study aims to identify the influence of slang usage on formal language proficiency among teenagers. Using a qualitative approach, this research was conducted through observations and interviews with several students at the Perguruan Indonesia Raya Foundation in Bandung. The results indicate that excessive use of slang can decrease teenagers' formal language skills, particularly in writing and speaking. However, slang can also enrich linguistic variation among teenagers as a form of expression and social identity. Therefore, an appropriate educational strategy is needed to maintain a balance between slang and formal language usage among teenagers